The Resurrection of the Indigenous Values System in Post-Apartheid African Law: South Africa's Constitutional and Legislative Framework Revisited - Ndima, Dial Dayana (Southern African Public Law, 2017)
A constitution that recognises customary law in South Africa must prioritise indigenous African values in order to give direction to state institutions in their quest to mainstream the African worldview in legal interpretation. Its framework must ensure that the recognition of indigenous African institutions restores their cultural meaning which must, in turn, reflect custom and social practice as the roots for anchoring African concepts to their own frame of reference. In order to reverse the effects of cultural imperialism that generated the injustices of the past South Africa's constitutional framework must also serve as an injunction enjoining state institutions to choose the living version of African law as their point of departure whenever they respond to calls to pronounce upon issues of indigenous African jurisprudence. In the South African context this task must entail effecting a change in the role of interpretive institutions from their pre-constitutional culture of denigrating African culture under the alienating repugnancy dispensation towards refashioning African law with indigenous values as envisioned by the ethos of transformation. The extent to which the constitutional institutions can contribute towards rehabilitating African law from being the pole-cat of South African jurisprudence to a credible component of the country's justice system is the measure of their success in this difficult and unenviable mission. A clue to accomplishing this mission could be to develop a theory of re-indigenisation as a counterweight to the distorted jurisprudence that was developed by the discredited repugnancy clause of yester-year. Such a theory would persuade legal and constitutional interpreters to mainstream the African life-world to which to anchor the rules, principles, concepts and doctrines derived from the indigenous value system.